Knowledge and attitudes about euthanasia in nursing students - Murillo Chiliquinga, Carlos Elian; Sandoval Balarezo, Gessi Maribel (Enfermería Cuidándote, 2026)
Introduction: Euthanasia is the act of intentionally ending a person's life, with the purpose of relieving the suffering of the person suffering from a terminal or painful illness. Greater knowledge promotes informed decisions and empathetic support, while personal beliefs can lead to compassionate support or emotional conflict.Objective: To analyze the knowledge and attitudes about euthanasia in nursing students.Methods: Quantitative approach, non-experimental design, descriptive scope and cross-sectional cohort. The population consisted of 102 sixth and seventh semester students, to whom a questionnaire on knowledge and attitudes towards euthanasia was applied that addressed four sections.Results: 99% of the students have knowledge about bioethics, 54% report that they have completed university studies on bioethics, 92% have heard, seen or read a case of euthanasia and finally 91% are in favor of euthanasia. It was identified that 75.3% of those surveyed had a high level of knowledge about euthanasia and 52.6% had a low level of knowledge regarding opinions about attitudes. The research showed that there is a correlation between the level of knowledge and attitudes towards euthanasia.Conclusions: The analysis of the attitudes of Nursing students towards euthanasia revealed a variety of opinions, from favorable positions to rejections, despite the fact that they had knowledge about legal, ethical and medical aspects related to euthanasia.
Keywords: Attitudes; Bioethics; Euthanasia; Knowledge